ANSWER
![a = - 7](https://tex.z-dn.net/?f=a%20%3D%20%20-%207)
![b = 1](https://tex.z-dn.net/?f=b%20%3D%201)
![c = 4](https://tex.z-dn.net/?f=c%20%3D%204)
EXPLANATION
The given quadratic equation is:
![0 = 4 - 7 {x}^{2} + x](https://tex.z-dn.net/?f=0%20%3D%204%20-%207%20%7Bx%7D%5E%7B2%7D%20%20%2B%20x)
We rewrite in the standard quadratic equation form to obtain,
![- 7 {x}^{2} + x + 4 = 0](https://tex.z-dn.net/?f=%20-%207%20%7Bx%7D%5E%7B2%7D%20%20%2B%20x%20%2B%204%20%3D%200)
Comparing this to the general standard quadratic equation.
![a {x}^{2} + bx + c = 0](https://tex.z-dn.net/?f=a%20%7Bx%7D%5E%7B2%7D%20%20%2B%20bx%20%2B%20c%20%3D%200)
We have my
![a = - 7](https://tex.z-dn.net/?f=a%20%3D%20%20-%207)
![b = 1](https://tex.z-dn.net/?f=b%20%3D%201)
![c = 4](https://tex.z-dn.net/?f=c%20%3D%204)
The answer is 46.125 hope this helped :)
Answer:
range: {y | y>= -8)
Step-by-step explanation:
We have a radical here.
y = root( x + 1) - 8
y is defined as long as x+1 >= 0
so domain must be x > -1
y values would start from -8
and go upward.
range: {y | y>= -8)
Answer:
![R=\frac{QJ}{I^2t}](https://tex.z-dn.net/?f=R%3D%5Cfrac%7BQJ%7D%7BI%5E2t%7D)
Step-by-step explanation:
So we have the equation:
![Q=\frac{I^2Rt}{J}](https://tex.z-dn.net/?f=Q%3D%5Cfrac%7BI%5E2Rt%7D%7BJ%7D)
And we want to solve for R.
First, let's multiply both sides by J to remove the fraction on the right. So:
![(J)Q=(J)\frac{I^2Rt}{J}](https://tex.z-dn.net/?f=%28J%29Q%3D%28J%29%5Cfrac%7BI%5E2Rt%7D%7BJ%7D)
Simplify the right:
![JQ=I^2Rt](https://tex.z-dn.net/?f=JQ%3DI%5E2Rt)
We can rewrite our equation as:
![JQ=R(I^2t)](https://tex.z-dn.net/?f=JQ%3DR%28I%5E2t%29)
So, to isolate the R variable, divide both sides by I²t:
![\frac{JQ}{I^2t}=\frac{R(I^2t)}{I^2t}](https://tex.z-dn.net/?f=%5Cfrac%7BJQ%7D%7BI%5E2t%7D%3D%5Cfrac%7BR%28I%5E2t%29%7D%7BI%5E2t%7D)
The right side cancels, so:
![R=\frac{QJ}{I^2t}](https://tex.z-dn.net/?f=R%3D%5Cfrac%7BQJ%7D%7BI%5E2t%7D)
And we are done!